Tinjauan Yuridis Terhadap Pernikahan Beda Agama (Studi Penetapan Mahkamah Agung Nomor 916/Pdt.P/2022/PN.Sby) - Fitria Annisa; Arista Candra Irawati (Universitas Ngudi Waluyo, 2024)
As a country that believes in One Almighty God, marriage in Indonesia is regulated in Law Number 1 of 1974 concerning Marriage, which does not recognize the validity of interfaith marriages. As a result, interfaith marriage is no longer a new phenomenon and is now recognized as a major social problem. The author examines the legal considerations made by the Surabaya District Court judge in the case of an interfaith marriage permit application using empiric juridical techniques. In the author's view, the judge has explained that there are legal rules that do not accept the validity of interfaith marriages. However, the judge did not consider the implications of interfaith marriage from a philosophical point of view. Law Number 23 of 2006 concerning Population Administration which is used as a legal consideration does not explain the validity of marriage as a component of religious ceremonies to provide legal certainty. The judge's decision in this case was only effective in carrying out the trial program by rejecting religious arguments from religious institutions which could make people less obedient in practicing their religion. Abstrak Sebagai negara yang berketuhanan Yang Maha Esa, pernikahan di Indonesia diatur dalam Undang-Undang Nomor 1 Tahun 1974 tentang Perkawinan, yang tidak mengakui keabsahan pernikahan beda agama. Akibatnya, perkawinan beda agama bukan lagi merupakan fenomena baru dan sekarang diakui sebagai masalah sosial yang besar. Penulis meneliti pertimbangan hukum yang dibuat oleh hakim Pengadilan Negeri Surabaya dalam perkara permohonan izin perkawinan beda agama dengan menggunakan teknik yuridis empiris. Menurut pandangan penulis, hakim telah menjelaskan bahwa ada aturan hukum yang tidak menerima keabsahan perkawinan beda agama. Namun, hakim tidak mempertimbangkan implikasi perkawinan beda agama dari sudut pandang filosofis. Undang-Undang Nomor 23 Tahun 2006 Tentang Administrasi Kependudukan yang digunakan sebagai pertimbangan hukum tidak menjelaskan keabsahan perkawinan sebagai salah satu komponen upacara keagamaan untuk memberikan kepastian hukum. Putusan hakim dalam perkara ini hanya efektif dalam menjalankan program persidangan dengan menolak dalil-dalil agama dari lembaga agama yang dapat membuat masyarakat kurang taat menjalankan agamanya.